Nanotechnology applications of flavonoids for viral diseases - Jannat, K; Alok Paul; Bondhon, TA; Hasan, A; Nawaz, M; Jahan, R; Mahboob, T; Nissapatorn, V; Wilairatana, P; de Lourdes Pereira, M; Rahmatullah, M (2021)
Recent years have witnessed the emergence of several viral diseases, including various zoonotic diseases such as the current pandemic caused by the Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2). Other viruses, which possess pandemic-causing potential include avian flu, Ebola, dengue, Zika, and Nipah virus, as well as the re-emergence of SARS (Severe Acute Respiratory Syndrome) and MERS (Middle East Respiratory Syndrome) coronaviruses. Notably, effective drugs or vaccines against these viruses are still to be discovered. All the newly approved vaccines against the SARS-CoV-2-induced disease COVID-19 possess real-time possibility of becoming obsolete because of the development of ‘variants of concern’. Flavonoids are being increasingly recognized as prophylactic and therapeutic agents against emerging and old viral diseases.Around 10,000 natural flavonoid compounds have been identified, being phytochemicals, all plant-based. Flavonoids have been reported to have lesser side effects than conventional anti-viral agents and are effective against more viral diseases than currently used anti-virals. Despite their abundance in plants, which are a part of human diet, flavonoids have the problem of low bioavailability. Various attempts are in progress to increase the bioavailability of flavonoids, one of the promising fields being nanotechnology. This review is a narrative of some anti-viral dietary flavonoids, their bioavailability, and various means with an emphasis on the nanotechnology system(s) being experimented with to deliver anti-viral flavonoids, whose systems show potential in the efficient delivery of flavonoids, resulting in increased bioavailability.